GE_GERICHTE P/22054/2020 vom 31. Mai 2022 - GE Cour de justice (2022)
MESURE THÉRAPEUTIQUE INSTITUTIONNELLE;PARTIE À LA PROCÉDURE;PARTIE CIVILE;RETRAIT(VOIE DE DROIT) | CPP.10; cp.59; CO.47; CO.59; CPP.120.al1; CP.66A